Learning Patterns of Generation Z Students in Memorizing the Al-Quran: Between Academic Discipline and Qur'anic Spirituality - Murtafiah, Nuroh (Universitas Negeri Padang, 2025)
This article examines the learning patterns of memorizing the Qur'an in the context of Islamic boarding schools and lectures, with a focus on generation Z students who have unique characteristics in receiving learning. This study uses a descriptive qualitative approach through observation, interviews and documentation. The results of the study show that Islamic boarding schools integrate academic learning on campus and discipline learning in Islamic boarding schools by instilling ur'ani spirituality as a representation of learning to memorize the Qur'an. The challenges in both activities are time management and boredom, so that Islamic boarding schools facilitate students to carry out activities outside of Islamic boarding school activities from 07.00 to 18.00 and besides that is the time devoted to activities at Islamic boarding schools. Thus, the integration of the tahfidz learning pattern that is spiritually based on the Qur'an with a systematic lecture pattern can produce a tahfidz learning model that is adaptive and flexible to the needs of Gen Z. This article recommends the need for innovation in Al-Qur'an learning strategies that combine the strengths of Islamic boarding schools and lectures in order to produce graduates who excel in religious and academic aspects.